Are They Just Two Children COVID-19 Cases Confused With Flu? - Zou, Biao; Ma, Di; Li, Yinhu; Qiu, Liru; Chen, Yu; Hao, Yan; Luo, Xiaoping; Shu, Sainan (Frontiers in Pediatrics, 2020)
COVID-19, an emerging infectious disease, has quickly spread all over the world. All human populations are susceptible to this disease. Here we present two pediatric COVID-19 cases, both of whom exhibited negative SARS-CoV-2 nucleic acid tests upon nasopharyngeal swab and were initially diagnosed with influenza A infection. COVID-19 was later confirmed in both patients by serum antibodies of SARS-CoV-2 and nucleic acid test on stool samples. Because children are susceptible to many respiratory pathogens, especially influenza, we concluded that children can be coinfected with multiple pathogens, and more attention should be paid to the exploration of SARS-CoV-2 during the pandemic of COVID-19. This report shows the possibility of misdiagnosis or missed diagnosis of children with COVID-19. We suggest that highly suspected pediatric COVID-19 cases with negative nucleic acid tests on nasopharyngeal swabs should be further checked by performing a nucleic acid test on stool samples and testing serum for antibodies against SARS-CoV-2.